ASSESSMENT OF FLOOD INCIDENCE AND ITS SOCIO-ECONOMIC IMPLICATIONS IN DAMATURU YOBE STATE, NIGERIA - Maina, Muhammed Bukar; Abba, B. M.; Isa, M. M. (FUDMA JOURNAL OF SCIENCES, 2022)
This paper assesses flood incidences and their socio-economic implications in Damaturu. The study examined people's awareness of the flashflood, determined the frequency of the menace far year, read the causes, assessed the effects of the problem and identified the control measures that were put in place. The study utilizes both primary and secondary data. The primary includes observation, interview, use of camera and questionnaire. In contrast, the secondary used relevant journals to justify the necessary findings. The study revealed that most of the respondents were aware of the existence of the flood. The study also showed that the menace used to occur more than once a year. Moreover, the study found that the primary cause of the flood includes Encroachments posed by human activities, heavy rainfall and poor drainage system. On the other hand, the study revealed that the significant effects of floods in the study area include damage to their houses and farmland. Lastly, the study found out that very few in the study area are using sandbags to limit the destruction, so 0it concludes by identifying the reasons for the flash floods as both natural and human induces; so finally, the study recommends the establishment of the functional hydrological office in Damaturu to monitor the flow of floods, Proper mapping of flood-prone zones, law enforcement and finally Government needs to encourage enlightenment about the wrong side of violating environment and help the victims that are affected by the flooding in the study area
Keywords: Damaturu, Flood, Socio-economic